Hamstring Pain and Muscle Strains Following Anterior Cruciate Ligament Reconstruction: A Prospective, Randomized Trial Comparing Hamstring Graft Harvest Techniques - D'Alessandro, Peter; Wake, Giulia; Annear, Peter (The Journal of Knee Surgery, 2013)
There is limited information in the literature regarding hamstring pain and muscle strains in patients following anterior cruciate ligament (ACL) reconstruction using hamstring autograft. We sought to investigate whether dividing hamstring tendons distal to the musculotendinous junction rather than forcefully stripping tendons away from the muscle belly during graft harvest resulted in a lower incidence of hamstring pain, muscle strains, and leg flexion strength deficit following commencement of sport-specific training postoperatively. Patients were randomized to either the “Cut” or “Push” groups of hamstring tendon harvesting. All other operative techniques were uniform. A total of 34 (cut = 20, push = 14) patients had a mean follow-up of 30 months, and assessments were conducted by a blinded single practitioner. A customized hamstring strain questionnaire and visual analogue pain score provided information for the study's primary focus: evaluation of postoperative hamstring pain and muscle strains. Leg flexion strength was also measured and a full knee assessment was conducted. The Cincinnati sports activity rating scale (SARS) was used to account for varying degrees of sporting participation and intensity since reconstruction. The “Cut” group's mean visual analogue score was 10.05 mm, significantly lower than the “Push” group (24.66 mm, p = 0.0398). The Cut group also recorded a significant reduction in the incidence of hamstring strains following ACL reconstruction (5/20 patients 25%) compared with the Push group (7/14 patients 50%, p = 0.045). There was no difference in leg flexion strength between the groups. Of the patients who reported hamstring strains, there was no significant difference in the mean Cincinnati SARS between the groups, nor any difference in overall knee function. The incidence of hamstring pain and muscle strains was significantly reduced in patients receiving the “cut” technique of harvesting hamstring tendons in ACL reconstruction surgery, a difference that was not attributable to a lower level of sporting activity.
Keywords: ACL reconstruction; hamstring graft; hamstring strains; muscle pain; donor site morbidity